Electrochemical behaviour of some organometallic compounds containing iron and molybdenum - Daries, Keith Louis (Department of Chemistry, 2016)
The electrochemical behaviour of some mononuclear alkyl compounds of the types CpFe(CO)₂(CH₂)nCH₃ (n = 0 to 11, Cp = η-C₅H₅), CpMo(CO)₃(CH₂)nCH₃ (n = 3,4,17) have been investigated in aprotic solvents. The cyclic voltammograms obtained for all the iron alkyl compounds suggest similar behaviour after the initial oxidation. The oxidation potentials showed no linear correlation with the corresponding lengths of the alkyl chain, but could, however, be interpreted with the available Tolman's χ-values. The subsequent CO insertion reaction to give an acyl species was found to be dependent on the nucleophilicity of the solvent. The relative rates of decarbonylation of the acyl species could be assessed through cyclic voltammetry. The electrochemical behaviour of heterobimetallic complexes of the type CpFe(CO)₂(CH₂)nMo(CO)₃Cp (n = 3 to 6) was found to be solvent dependent. The anodic waves obtained for these complexes in acetonitrile showed up as two closely spaced waves. Our results suggest that the two metals in CpFe(CO)₂(CH)nMo(CO)₃Cp behave independently, with the iron end of the molecule being oxidized first, followed by CO insertion/alkyl migration at this end.